Perception of Organizational Justice and Home Office Work Performance: Influence of Affective Commitment - Martins, Andreia Dulce; Euzebio, Larissa Dalla Corte; Beuren, Ilse Maria (Review of Business Management, 2023)
Purpose – This article examines the effect of perceived organizational justice on home office work performance, mediated by affective commitment. Theoretical framework – The theoretical lens used to support this research is organizational justice, in its distributive, procedural, and interactional dimensions. Design/methodology/approach – A single entity survey was carried out in a credit union, and structural equation modeling was used to analyze the 112 valid responses. Findings – The results reveal that the perception of distributive justice has a significant effect on home office work performance, in contrast to perceptions of procedural and interactional justice. Perceptions of distributive and procedural justice had a significant effect on affective commitment, but interactional justice did not. Nevertheless, affective commitment does not seem to influence home office work performance, and no mediating effect of affective commitment was confirmed. Practical & social implications of research – The study confirms the effect of distributive and procedural justice, but not of interactional justice, on affective commitment, and does not confirm the influence of commitment. Conclusions – The findings suggest that home office work increased the perception of distributive justice and decreased affective commitment to the credit union studied, given that it did not have a significant effect on job performance. Originality/value – Based on the literature, the relationship between the dimensions of organizational justice and home office work performance was examined. The findings encourage actions to promote perceptions of justice and increase the level of affective commitment in the credit union studied. Keywords: organizational justice, affective commitment, job performance, working from home.